ACCESS TO HEALTH SERVICES BY THE COMMUNITY DURING COVID-19 PANDEMIC - Wijaya, Dian Rezki; Bujawati, Emmi; Widiastuty, Lilis; Wardani, Sukma; Islamiyah, Andi; Meriam, Andi; Pisagau, Farhana Azzahra (Homes Journal: Hospital Management Studies Journal, 2022)
Background: During the current covid-19 pandemic, public visits to health facilities such as hospitals, health centers and clinics have decreased. People are increasingly worried about visiting health facilities for fear of being infected. Objective: The purpose of this study was to measure the level of public concern about visiting health facilities during the pandemic when experiencing health problems. Method: This research is a quantitative research using an analytical approach and a cross sectional. The population in this study were all Indonesian people and the number of samples in this study was 118 people.sampling technique used was accidental sampling technique. Result: The results showed that the level of public knowledge about covid-19 showed that people with a low level of knowledge were 14 people (11.9%) and a high level of knowledge was 104 (88.1%). Respondents with the level of public concern visiting health facilities showed that their level of concern was low as many as 25 people (21.2%), moderate 40 people (33.9%) and high 53 (44.9%). There is no relationship between the level of knowledge with the level of public concern visiting health facilities with a p value 0.421. Conclusion: Public knowledge about COVID-19 is in the high category and the level of public concern for visiting health facilities during the pandemic is in the low category and there is no relationship between the level of public knowledge and the level of public concern for visiting health facilities